Predicting the Disciplinary Adjustment of Maximum and Minimum Security Prison Inmates Using the Lifestyle Criminality Screening Form - Walters, Glenn D. (International journal of offender therapy and comparative criminology, 1991)
Using a person-environment fit paradigm it was reasoned that the lifestyle criminal adjusts best in environments which are highly structured. In the first of two studies examining this issue, it was determined that the Lifestyle Criminality Screening Form (LCSF), a putative measure of lifestyle criminality, successfully discriminated between disciplinary and nondisciplinary inmates in a less structured situation (minimum security) but not in a more highly structured situation (maximum security). In a second study, successively sampled inmates were organized according to their scores on the LCSF and compared as to the number of disciplinary reports received within a six-month period. Results of this second study revealed that the total LCSF score predicted disciplinary problems in the minimum security facility but not in the maximum security penitentiary. These findings tend to support the validity of the LCSF, as well as the hypothesis that lifestyle criminals may have problems functioning in environments which are less than maximally structured